2018
DOI: 10.1177/0963689718782442
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Adipose-Derived Stem Cells and Recombinant Peptide Pieces on Mouse Model of DSS Colitis

Abstract: Cell therapies using adipose-derived stem cells (ADSCs) have been used to treat inflammatory bowel disease (IBD) in human and dog. We previously reported the CellSaic technique, which uses a recombinant scaffold to enhance the efficacy of cell therapy. To examine whether this technique can be applied to cell therapy for colitis, we evaluated the efficacy of CellSaic in colitis mouse models. Colitis mouse models were developed by administering dextran sulfate sodium (DSS) to C57BL/6 mice for 7 days. Then CellSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is known that MSCs secrete anti-inflammatory cytokines (IL-10, TGF-α, IDO, TSG-6, etc.) [15][16][17]31], and we have confirmed that MSC CellSaics secreted 3.1-fold more anti-inflammatory cytokine TSG-6 in response to concentration of inflammatory cytokine TNF-α than the MSC spheroids [20]. In reference [34], it is reported that transplantation of ALG-PLO microencapsulated islets trigger inflammation by increasing the TNF-α concentration at the transplantation site.…”
Section: Discussionsupporting
confidence: 66%
“…Mesenchymal stem cells (MSCs) are promising options as the cells comprising CellSaics for subcutaneous transplantation since they have revascularization, anti-inflammatory, and immunomodulatory abilities [14][15][16][17] and are known to enhance islet function when co-transplanted with them [18,19]. Our previous study demonstrated the continuous release of angiogenic factors and anti-inflammatory cytokines via a combination of MSCs and CellSaics (MSC CellSaics) [13,20]. Furthermore, the subcutaneous co-transplantation of the MSC CellSaics and islets into immunodeficient mice was shown to have higher therapeutic efficiency compared to co-transplantation of MSCs and islets [13].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its anti-inflammatory properties, ASC transplantation has appeared to be an effective method for treatment of inflammatory bowel diseases in animal models [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. It was found that ASC administration significantly reduced the secretion of proinflammatory cytokines (tumor necrosis factor-α, interleukin-12, and vascular endothelial growth factor), and improved the clinical disease score and histological parameters in experimentally induced models of murine colitis [ 103 , 104 , 105 , 108 , 109 , 110 ]. The ASC infusion resulted in a decrease in both clinical inflammatory bowel disease activity index and canine chronic enteropathy clinical activity index, in a group of treated dogs.…”
Section: Clinical Applications Current and Perspectivesmentioning
confidence: 99%
“…MSC-CellSaic enhances the function of microencapsulated pancreatic islets by inducing angiogenesis and suppressing the inflammatory response. It was previously reported that the anti-inflammatory effect of MSC-CellSaic was enhanced over that of non-CellSaic MSCs [ 25 ]. Making MSCs CellSaic secretes more of the anti-inflammatory cytokine TSG-6, which is an important cytokine that exerts its effects in various inflammatory models [ 26 ].…”
Section: Discussionmentioning
confidence: 99%